Acrylic resin, and adhesive composition, adhesive, adhesive film, masking adhesive, and masking adhesive film made using the same
Patent Information
- Application Number
- JP2021035504
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-05
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2041-03-05
AI Technical Summary
【0011】 本発明のアクリル系樹脂(A)は、湿潤面に貼った場合においても充分な粘着力を有し、さらにマスキング用粘着剤として用いた場合に、被着体表面に、糊残りのない被着体耐汚染性に優れる粘着剤を得ることができる。そのため、上記アクリル系樹脂を用いてなる粘着剤組成物、粘着剤、粘着フィルム、マスキング用粘着剤、およびマスキング用粘着フィルムは、水中や湿潤条件下での使用において優れた粘着性能を発揮することができる。
Smart Images

Figure 0007635583000001 
Figure 0007635583000002 
Figure 0007635583000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an acrylic resin, and a pressure-sensitive adhesive composition, a pressure-sensitive adhesive, a pressure-sensitive adhesive film, a masking pressure-sensitive adhesive, and a masking pressure-sensitive adhesive film using the same. More specifically, the present invention relates to an acrylic resin that can obtain sufficient adhesive performance even in water or under wet conditions, a pressure-sensitive adhesive composition using the same, a pressure-sensitive adhesive such as a masking pressure-sensitive adhesive obtained by crosslinking the pressure-sensitive adhesive composition, and a pressure-sensitive adhesive film such as a masking pressure-sensitive adhesive film having a pressure-sensitive adhesive layer made of the pressure-sensitive adhesive. [Background technology]
[0002] In recent years, adhesive tapes have been used in various industrial fields such as home appliances, automobiles, office automation equipment, and construction as a joining means with good workability and high adhesive reliability. As a new performance, it is preferable that the tape can exhibit sufficient adhesive performance even under water or wet conditions. However, it is generally difficult to exhibit sufficient adhesive performance when the surface of the object to be bonded is wet.
[0003] As an example of an adhesive tape to be used under water or under wet conditions, Patent Document 1 discloses an aqueous dispersion type adhesive composition and adhesive product that can exhibit good initial adhesive strength to condensation-covered or wet surfaces and has excellent constant-load peel strength, the aqueous dispersion type adhesive composition being characterized in that it contains 0.5 to 15 parts by weight of a specific hydrophilic polymer per 100 parts by weight of the solid content of the acrylic or rubber aqueous dispersion type adhesive composition.
[0004] However, since this is a water-dispersed PSA composition that uses a water-soluble resin as a dispersant, there is a risk that the PSA will dissolve in water and will not be able to maintain its adhesive performance if used for a long period of time.
[0005] Patent Document 2 discloses an adhesive sheet for application to wet surfaces that can reliably and easily place an object to be attached on a wet surface, in which a water-absorbing layer is provided on one side of the adhesive layer, and by providing gaps in the adhesive layer, moisture on the wet surface is absorbed by the water-absorbing layer, thereby exhibiting good adhesive strength. However, because there are gaps in the adhesive layer, the adhesive strength may decrease.
[0006] Furthermore, the technologies disclosed in Patent Documents 1 and 2 above do not take into consideration at all the contamination resistance of the adherend, that is, preventing adhesive residue and the occurrence of adhesive marks on the surface of the adherend when the adhesive is used as a temporary protective (masking) adhesive, adhered to the adherend, and then peeled off. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2003-313525 A [Patent Document 2] JP 2017-160344 A Summary of the Invention [Problem to be solved by the invention]
[0008] In view of the above, the present invention aims to provide an acrylic resin that has sufficient adhesive strength even when applied to a wet surface, and that, when used as a masking adhesive, makes it possible to obtain an adhesive that leaves no adhesive residue on the surface of the adherend and has excellent resistance to contamination of the adherend. Another aim of the present invention is to provide an adhesive composition, an adhesive, an adhesive film, an adhesive for masking, and an adhesive film for masking, each using such an acrylic resin. [Means for solving the problem]
[0009] The present inventors have conducted extensive research to solve the above problems. During the course of research, they discovered that when the copolymerization component (a) constituting the acrylic resin (A), which is a material of the pressure-sensitive adhesive composition, contains new acrylic monomers (a1-1) and (a1-2) that have not been used before, the adhesive performance in water or under wet conditions is dramatically improved, and thus they have arrived at the present invention.
[0010] Therefore, the gist of the present invention is the following [1] to [7]. [1] An acrylic resin (A) obtained by copolymerizing a copolymerization component (a) containing an acrylic monomer (a1-1) represented by the following chemical formula (1) and / or an acrylic monomer (a1-2) represented by the following chemical formula (2): [ka] [ka] [2] The acrylic resin (A) according to claim 1, wherein the total proportion of the acrylic monomer (a1-1) and the acrylic monomer (a1-2) in the copolymerization component (a) is 0.01 to 50% by weight. [3] A pressure-sensitive adhesive composition comprising the acrylic resin (A) according to [1] or [2] and a crosslinking agent (B). [4] A pressure-sensitive adhesive obtained by crosslinking the pressure-sensitive adhesive composition described in [3]. [5] An adhesive film having an adhesive layer made of the adhesive described in [4]. [6] A masking adhesive, characterized by using the adhesive described in [4]. [7] A masking adhesive film, characterized by using the adhesive described in [4]. Effect of the Invention
[0011] The acrylic resin (A) of the present invention has sufficient adhesive strength even when applied to a wet surface, and when used as a masking adhesive, it is possible to obtain an adhesive that leaves no adhesive residue on the surface of the adherend and has excellent resistance to contamination of the adherend. Therefore, the adhesive composition, adhesive, adhesive film, masking adhesive, and masking adhesive film made using the above acrylic resin can exhibit excellent adhesive performance when used in water or under wet conditions. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present invention will be described in detail below, but these are merely examples of preferred embodiments. In addition, "(meth)acrylic" means acrylic or methacrylic, "(meth)acryloyl" means acryloyl or methacryloyl, and "(meth)acrylate" means acrylate or methacrylate. In addition, "acrylic resin" is a resin obtained by polymerizing a polymerization component containing at least one (meth)acrylate monomer. In addition, the "adhesive" in this invention is one that has tack at 25°C (room temperature) and adheres to an adherend with light pressure, such as that applied by hand, and the "film" conceptually encompasses sheets, films, and tapes.
[0013] <Acrylic resin (A)> As described above, the acrylic resin (A) of the present invention is obtained by copolymerizing a copolymerization component (a) containing an acrylic monomer (a1-1) represented by the following chemical formula (1) (hereinafter, may be simply referred to as monomer (a1-1)) and / or an acrylic monomer (a1-2) represented by the following chemical formula (2) (hereinafter, may be simply referred to as monomer (a1-2)), and optionally containing a copolymerizable monomer (a2) having a hydroxyl group and / or a carboxy group, excluding the monomers (a1-1) and (a1-2) (hereinafter, may be simply referred to as monomer (a2)), and a (meth)acrylic acid alkyl ester monomer (a3) having an alkyl group having 4 to 20 carbon atoms (hereinafter, may be simply referred to as monomer (a3)).
[0014] [Monomer (a1-1), Monomer (a1-2)] The monomer (a1-1) is an acrylic monomer represented by the following chemical formula (1): The monomer (a1-2) is an acrylic monomer represented by the following chemical formula (2):
[0015] [ka]
[0016] [ka]
[0017] In the monomers (copolymerization components (a)) constituting the acrylic resin (A), the monomers (a1-1) and (a1-2) may be used alone or in combination. From the viewpoint of improving the adhesive performance in water or under wet conditions required in the present invention, the total proportion of the acrylic monomer (a1-1) and the acrylic monomer (a1-2) relative to the entire copolymerization component (a) is preferably 0.01 to 50% by weight, more preferably 0.1 to 40% by weight, even more preferably 0.5 to 30% by weight, and particularly preferably 0.9 to 20% by weight.
[0018] From the viewpoint of improving the adhesive performance in water or under wet conditions required in the present invention, the total proportion of the acrylic monomer (a1-1) and the acrylic monomer (a1-2) in the acrylic resin (A) is preferably 0.01 to 50 mol %, more preferably 0.05 to 20 mol %, even more preferably 0.1 to 10 mol %, and particularly preferably 0.5 to 3 mol %.
[0019] Here, the above-mentioned monomer (a1-1) and monomer (a1-2) can be obtained, for example, as shown in the following synthesis examples.
[0020] [Production of acrylic monomer (a1-1)] The acrylic monomer (a1-1) can be synthesized, for example, by obtaining methanesulfonate-2-ethyl methacrylate by mesylation of 2-hydroxyethyl methacrylate, and then reacting the methanesulfonate-2-ethyl methacrylate with gallic acid, as shown in the following reaction formula.
[0021] [ka]
[0022] The mesylation of 2-hydroxyethyl methacrylate is carried out by dissolving 2-hydroxyethyl methacrylate in a solvent such as tetrahydrofuran to obtain a mixture with triethylamine, and then adding methanesulfonyl chloride to the mixture to cause a reaction. The blending molar ratio of 2-hydroxyethyl methacrylate to methanesulfonyl chloride is 2-hydroxyethyl methacrylate:methanesulfonyl chloride=about 1:1.1 to 1:1.3.
[0023] By removing the solvent from the mixed solution after the above reaction, methanesulfonate-2-ethyl methacrylate (yellow liquid) can be obtained.
[0024] In addition, the above-mentioned yellow liquid 1 The results of the H NMR analysis are as follows: 1 H NMR (400MHz, CDCl3): δ=6.08(s, 1H), 5.57-5.54(m, 1H), 4.41-4.37(m, 2H), 4.35-4.31(m, 2H), 2.98(s, 3H), 1.88(s, 3H)
[0025] Next, a solution of gallic acid, sodium bicarbonate, and dimethyl sulfoxide (DMSO) is prepared, and methanesulfonate-2-ethyl methacrylate is added and reacted. The blending molar ratio of methanesulfonate-2-ethyl methacrylate and gallic acid is methanesulfonate-2-ethyl methacrylate:gallic acid=about 1:1.1 to 1:1.3. Thereafter, the solvent is removed, the residue is purified by column chromatography, and then recrystallized from a solution of ethyl acetate / n-heptane to obtain the acrylic monomer (1-a) (white solid).
[0026] In addition, the above white solid 1 The results of the H NMR analysis are as follows: 1 H NMR (400MHz, DMSO-d6): δ=9.22(s, 3H), 6.94(s, 2H), 6.05-6.02(m, 1H), 5.71-5.67(m, 1H), 4.46-4.36(m, 4H), 1.87(t, 3H)
[0027] [Production of acrylic monomer (a1-2)] The acrylic monomer (a1-2) can be synthesized, for example, by reacting 4-(chloroacetyl)catechol with methacrylic acid as shown in the following formula.
[0028] [ka]
[0029] 4-(Chloroacetyl)catechol methacrylic acid and methacrylic acid are dissolved in a solvent such as acetonitrile to obtain a mixed solution. Triethylamine is added to the resulting mixed solution to cause a reaction. The molar ratio of methacrylic acid to 4-(chloroacetyl)catechol is about 1:0.4 to 1:0.6 (methacrylic acid:4-(chloroacetyl)catechol). The solvent is removed from the mixed solution after the reaction, and the resulting solution is purified by column chromatography to obtain the acrylic monomer (1-b) (white solid).
[0030] In addition, the above white solid 1The results of the H NMR analysis are as follows: 1 H NMR (400MHz, DMSO-d6): δ=10.45-9.27(m, 2H), 7.43-7.28(m, 2H), 6.84(d, 1H), 6.12(s, 1H), 5.77(t, 1H), 5.42(s, 2H), 1.93(s, 3H)
[0031] [Monomer (a2)] The copolymerizable monomer (a2) having a hydroxyl group and / or a carboxyl group may be used alone or in combination of two or more kinds. From the viewpoint of adhesion to an adherend, the monomer (a2) is preferably (meth)acrylic acid or a (meth)acrylate monomer, and more preferably (meth)acrylic acid. Examples of copolymerizable monomers having a hydroxyl group include (meth)acrylic acid hydroxyalkyl esters such as 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 5-hydroxypentyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, and 8-hydroxyoctyl (meth)acrylate; caprolactone-modified monomers such as caprolactone-modified 2-hydroxyethyl (meth)acrylate; oxyalkylene-modified monomers such as diethylene glycol (meth)acrylate and polyethylene glycol (meth)acrylate; primary hydroxyl group-containing monomers such as 2-acryloyloxyethyl-2-hydroxyethyl phthalate; secondary hydroxyl group-containing monomers such as 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 3-chloro 2-hydroxypropyl (meth)acrylate; and tertiary hydroxyl group-containing monomers such as 2,2-dimethyl 2-hydroxyethyl (meth)acrylate. Among these, primary hydroxyl group-containing monomers are preferred because of their excellent reactivity with crosslinking agents, and 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are particularly preferred. Furthermore, examples of copolymerizable monomers having a carboxy group include (meth)acrylic acid, 2-(meth)acryloyloxyethyl hexahydrophthalic acid, 2-(meth)acryloyloxypropyl hexahydrophthalic acid, 2-(meth)acryloyloxyethyl phthalic acid, 2-(meth)acryloyloxypropyl phthalic acid, 2-(meth)acryloyloxyethyl maleic acid, 2-(meth)acryloyloxypropyl maleic acid, 2-(meth)acryloyloxyethyl succinic acid, 2-(meth)acryloyloxypropyl succinic acid, crotonic acid, fumaric acid, maleic acid, itaconic acid, monomethyl maleate, and monomethyl itaconate. Among these, acrylic acid is preferred from the standpoint of adhesion and stability during polymerization.
[0032] The proportion of the monomer (a2) relative to the total copolymerization components (a) constituting the acrylic resin (A) is preferably 0.1 to 30% by weight, more preferably 0.5 to 25% by weight, even more preferably 1 to 20% by weight, and particularly preferably 3 to 15% by weight.
[0033] [Monomer (a3)] As the (meth)acrylic acid alkyl ester monomer (a3), a (meth)acrylic acid alkyl ester monomer having an alkyl group having 1 to 20 carbon atoms is usually used, preferably a (meth)acrylic acid alkyl ester monomer having an alkyl group having 2 to 10 carbon atoms, and more preferably a (meth)acrylic acid alkyl ester monomer having an alkyl group having 4 to 8 carbon atoms. Specific examples of the monomer (a3) include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isodecyl (meth)acrylate, tridecyl (meth)acrylate, n-lauryl (meth)acrylate, etc. Among these, n-butyl (meth)acrylate and 2-ethylhexyl (meth)acrylate are preferred from the viewpoints of excellent adhesive properties and excellent stability during polymerization, and n-butyl acrylate is more preferred. These monomers can be used alone or in combination of two or more kinds.
[0034] The proportion of the monomer (a4) relative to the total copolymerization components (a) constituting the acrylic resin (A) is preferably 60 to 99.9% by weight, more preferably 70 to 98% by weight, even more preferably 80 to 97% by weight, and particularly preferably 85 to 95% by weight.
[0035] [Monomer (a4)] Moreover, a monomer (a4) other than (a1) to (a3) may be optionally contained within a range that does not impair the effects of the present invention. For example, acid anhydride group-containing vinyl monomers such as maleic anhydride and itaconic anhydride; epoxy group-containing vinyl monomers such as glycidyl (meth)acrylate, glycidyl α-ethyl acrylate, and 3,4-epoxybutyl (meth)acrylate; amino group-containing (meth)acrylate vinyl monomers such as dimethylaminoethyl (meth)acrylate and diethylaminoethyl (meth)acrylate; (meth)acrylamide, Nt-butyl (meth)acrylamide, N-methylol (meth)acrylamide, N-methoxymethyl (meth)acrylamide, N-butoxymethyl (meth)acrylamide, diacetone acrylamide, and maleic acid amine. vinyl monomers containing an amide group, such as maleimide and styrene; vinyl monomers such as styrene, α-methylstyrene, vinyl toluene, (meth)acrylonitrile, vinyl chloride, vinyl acetate, and vinyl propionate; divinylbenzene, ethylene glycol di(meth)acrylate, 1,3-butylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and allyl (meth)acrylate. The other monomers (a3) may be used alone or in combination of two or more.
[0036] The content of the monomer (a4) relative to the total copolymerization component (a) constituting the acrylic resin (A) is preferably 10% by weight or less, more preferably 5% by weight or less, and even more preferably 1% by weight or less.
[0037] [Production of acrylic resin (A)] The acrylic resin (A) used in the present invention can be produced by polymerizing the specific acrylic monomers (a1-1) and (a1-2) and / or the copolymerization component (a) containing other monomers by, for example, mixing or dropping a polymerization initiator into an organic solvent.
[0038] The polymerization reaction can be carried out by a conventionally known polymerization method such as solution radical polymerization, suspension polymerization, bulk polymerization, emulsion polymerization, etc., and among these, solution radical polymerization and bulk polymerization are preferred, and solution radical polymerization is more preferred.
[0039] Examples of the organic solvent used in the polymerization reaction include aromatic hydrocarbons such as toluene and xylene, aliphatic hydrocarbons such as hexane, esters such as ethyl acetate and butyl acetate, aliphatic alcohols such as n-propyl alcohol and isopropyl alcohol, and ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone.
[0040] Among these organic solvents, ethyl acetate, acetone, methyl ethyl ketone, butyl acetate, toluene, and methyl isobutyl ketone are preferably used, and more preferably ethyl acetate, acetone, and methyl ethyl ketone, in view of the ease of polymerization reaction, the effect of chain transfer, the ease of drying during adhesive coating, and high safety. These organic solvents may be used alone or in combination of two or more kinds. The amount of these organic solvents used is usually 10 to 900 parts by weight per 100 parts by weight of the copolymerization component (a) constituting the acrylic resin (A).
[0041] In addition, examples of the polymerization initiator used in such solution radical polymerization include azo initiators such as 2,2'-azobisisobutyronitrile, 2,2'-azobis-2-methylbutyronitrile, 4,4'-azobis(4-cyanovaleric acid), and 2,2'-azobis(methylpropionic acid), which are normal radical polymerization initiators, and organic peroxides such as benzoyl peroxide, lauroyl peroxide, di-t-butyl peroxide, and cumene hydroperoxide, which can be appropriately selected and used according to the monomer to be used. Among them, 2,2'-azobisisobutyronitrile is preferred in the present invention. These polymerization initiators may be used alone or in combination of two or more. The amount of these polymerization initiators used is usually 0.01 to 5% by weight based on the copolymerization component (a).
[0042] [Physical properties of acrylic resin (A)] The weight average molecular weight (Mw) of the acrylic resin (A) thus obtained is preferably 100,000 to 3,000,000, more preferably 200,000 to 2,000,000, even more preferably 300,000 to 1,800,000, and particularly preferably 350,000 to 1,600,000. If the weight average molecular weight is too small, durability tends to decrease, whereas if it is too large, a large amount of dilution solvent is required during preparation, drying properties decrease, and residual solvent increases in the pressure-sensitive adhesive layer, tending to decrease durability.
[0043] The dispersity (weight average molecular weight / number average molecular weight) of the acrylic resin (A) is preferably 20 or less, more preferably 15 or less, and further preferably 12 or less. If the degree of dispersion is too high, reworkability and durability tend to decrease. The lower limit of the degree of dispersion is usually 1.
[0044] The weight-average molecular weight (Mw) is the weight-average molecular weight calculated based on the molecular weight of standard polystyrene. The high-performance liquid chromatograph (Waters Corporation, "Waters 2695 (main body)" and "Waters 2414 (detector)") was equipped with a Shodex GPC KF-806L column (molecular weight exclusion limit: 2 × 10 7 , Separation range: 100~2×10 7 The measurement is performed by connecting three tubes in series: theoretical plate number: 10,000 plates / tube, filler material: styrene-divinylbenzene copolymer, filler particle size: 10 μm. The number average molecular weight is also measured in the same way, and the dispersity (weight average molecular weight / number average molecular weight) is calculated from the number average molecular weight and weight average molecular weight.
[0045] The glass transition temperature (Tg) of the acrylic resin (A) is preferably -70°C or higher, more preferably -60 to 10°C, even more preferably -55 to 0°C, and particularly preferably -52 to -10°C, from the standpoints of adhesive performance and contamination resistance of the adherend.
[0046] The glass transition temperature (Tg) of the acrylic resin (A) is a value measured using a differential scanning calorimeter "DSC Q2000" manufactured by TA Instruments, Inc. The measurement temperature range is -80 to 40°C, and the temperature rise rate is 5°C / min.
[0047] [Acrylic resin (A) solution] The acrylic resin (A) is usually adjusted in viscosity with a solvent or the like, and used in the pressure-sensitive adhesive composition of the present invention as a solution of the acrylic resin (A). The dilution concentration is preferably 5 to 60% by weight, more preferably 10 to 50% by weight, and even more preferably 30 to 45% by weight in terms of resin content. If the concentration is too high, the fluidity tends to decrease, making it difficult to handle, and if the concentration is too low, it tends to be difficult to apply the pressure-sensitive adhesive.
[0048] The viscosity of the acrylic resin (A) solution is preferably 100 to 30,000 mPa·s, more preferably 500 to 20,000 mPa·s, further preferably 1,000 to 15,000 mPa·s, and particularly preferably 1,300 to 10,000 mPa·s, from the viewpoint of ease of handling. If the viscosity is too high, the fluidity decreases and handling tends to become difficult, whereas if the viscosity is too low, application of the resulting adhesive tends to become difficult.
[0049] The viscosity of the acrylic resin (A) solution is measured by subjecting the resin solution, whose temperature has been adjusted to 25° C., to a rotational viscosimetry using a B-type viscometer.
[0050] <Adhesive composition> In order to improve adhesive residual properties and the durability of the adhesive, it is preferable that the pressure-sensitive adhesive composition of the present invention further contains a crosslinking agent (B) in addition to the acrylic resin (A).
[0051] [Crosslinking agent (B)] The crosslinking agent (B) used in the pressure-sensitive adhesive composition of the present invention reacts with the functional groups in the acrylic resin (A) to form a crosslinked structure, and examples thereof include epoxy-based crosslinking agents, isocyanate-based crosslinking agents, aziridine-based crosslinking agents, melamine-based crosslinking agents, aldehyde-based crosslinking agents, amine-based crosslinking agents, metal chelate-based crosslinking agents, etc. Among these, it is preferable to use an epoxy-based crosslinking agent because of its excellent adhesive performance and pot life. The crosslinking agent (B) may be used alone or in combination of two or more kinds.
[0052] Examples of the epoxy crosslinking agent include bisphenol A-epichlorohydrin type epoxy resins, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerin diglycidyl ether, glycerin triglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane triglycidyl ether, sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, pentaerythritol polyglycidyl erythritol, diglycerol polyglycidyl ether, 1,3'-bis(N,N-diglycidylaminomethyl)cyclohexane, and N,N,N',N'-tetraglycidyl-m-xylylenediamine. Among these epoxy crosslinking agents, polyfunctional epoxy resins such as 1,3'-bis(N,N-diglycidylaminomethyl)cyclohexane and N,N,N',N'-tetraglycidyl-m-xylylenediamine are preferred in terms of high reactivity.
[0053] Examples of the isocyanate-based crosslinking agent include aromatic isocyanate-based crosslinking agents such as tolylene diisocyanate-based crosslinking agents such as 2,4-tolylene diisocyanate and 2,6-tolylene diisocyanate, xylylene diisocyanate-based crosslinking agents such as 1,3-xylylene diisocyanate, diphenylmethane-4,4-diisocyanate and other diphenylmethane-based crosslinking agents, and naphthalene diisocyanate-based crosslinking agents such as 1,5-naphthalene diisocyanate; isophorone diisocyanate, 1,4-cyclohexane diisocyanate, and other diphenylmethane-based crosslinking agents. alicyclic isocyanate crosslinking agents such as hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, and the like; and adducts, biuret forms, and isocyanurates of the above-mentioned isocyanate compounds. Among these isocyanate-based crosslinking agents, tolylene diisocyanate-based crosslinking agents are preferred in terms of pot life and durability, xylylene diisocyanate-based crosslinking agents or isocyanurate skeleton-containing isocyanate-based crosslinking agents are preferred in terms of shortening the aging time, and aromatic ring-free isocyanate-based crosslinking agents are preferred in terms of yellowing resistance. Specifically, among these, tolylene diisocyanate, xylylene diisocyanate, an adduct of hexamethylene diisocyanate and trimethylolpropane, and a nurate are preferred in terms of excellent balance between durability, pot life, and crosslinking speed.
[0054] Examples of the aziridine-based crosslinking agent include tetramethylolmethane-tri-β-aziridinylpropionate, trimethylolpropane-tri-β-aziridinylpropionate, N,N'-diphenylmethane-4,4'-bis(1-aziridinecarboxamide), and N,N'-hexamethylene-1,6-bis(1-aziridinecarboxamide).
[0055] Examples of the melamine-based crosslinking agent include hexamethoxymethylmelamine, hexaethoxymethylmelamine, hexapropoxymethylmelamine, hexaptoxymethylmelamine, hexapentyloxymethylmelamine, hexahexyloxymethylmelamine, melamine resins, and the like.
[0056] Examples of the aldehyde crosslinking agent include glyoxal, malondialdehyde, succindialdehyde, maleic dialdehyde, glutaric dialdehyde, formaldehyde, acetaldehyde, and benzaldehyde.
[0057] Examples of the amine-based crosslinking agent include hexamethylenediamine, triethyldiamine, polyethyleneimine, hexamethylenetetraamine, diethylenetriamine, triethyltetraamine, isophoronediamine, amino resins, and polyamides.
[0058] Examples of the metal chelate crosslinking agent include coordination compounds of polyvalent metals such as aluminum, iron, copper, zinc, tin, titanium, nickel, antimony, magnesium, vanadium, chromium, and zirconium with acetylacetone or acetoacetyl ester.
[0059] When such a crosslinking agent (B) is used, its content is preferably 0.001 to 20 parts by weight, more preferably 0.01 to 15 parts by weight, even more preferably 0.05 to 10 parts by weight, and particularly preferably 0.09 to 5 parts by weight, relative to 100 parts by weight of the acrylic resin (A). If the content is too low, the removability tends to be easily reduced, whereas if the content is too high, the adhesion to the adherend tends to be reduced or long-term aging is required.
[0060] <Other ingredients> The pressure-sensitive adhesive composition of the present invention may contain other known additives, such as polyether compounds such as polyalkylene glycols such as polypropylene glycol, colorants, powders such as pigments, dyes, surfactants, plasticizers, tackifiers, surface lubricants, leveling agents, softeners, antioxidants, antiaging agents, light stabilizers, ultraviolet absorbers, polymerization inhibitors, inorganic or organic fillers, metal powders, particulate materials, foil-like materials, etc., which can be appropriately added depending on the application. In addition, a redox system in which a reducing agent is added may be adopted within a controllable range. These can be used alone or in combination of two or more. The amount of these additives is preferably 5 parts by weight or less, more preferably 3 parts by weight or less, and further preferably 1 part by weight or less, based on 100 parts by weight of the acrylic resin (A).
[0061] Thus, the pressure-sensitive adhesive composition of the present invention can be obtained by mixing the acrylic resin (A), preferably further the crosslinking agent (B), and further other optional components as required.
[0062] From the viewpoints of adhesion, removability, etc., the proportion of the acrylic resin (A) in the entire pressure-sensitive adhesive composition of the present invention is preferably 50% by weight or more, more preferably 60% by weight or more, even more preferably 70% by weight or more, and particularly preferably in the range of 80 to 99.9% by weight.
[0063] The mixing method is not particularly limited, and various methods can be used, such as a method of mixing the components all at once, or a method of mixing any of the components and then mixing the remaining components all at once or sequentially.
[0064] <Adhesive> The adhesive composition of the present invention becomes an adhesive by drying and / or crosslinking. Such an adhesive can exhibit sufficient adhesive performance even under water or wet conditions. Therefore, it can be suitably used as an adhesive for various members such as an adhesive for masking films, an adhesive for surface protection films, an adhesive for display labels, and an adhesive for masking tapes, and is particularly suitable for use as an adhesive for masking films, particularly as an adhesive for architectural masking films. In forming such a pressure-sensitive adhesive layer, when the crosslinking agent (B) is used, it is preferable to adjust the total amount of the crosslinking agent (B) added and to fully consider the effects of the crosslinking temperature and time.
[0065] The crosslinking temperature and time can be adjusted depending on the crosslinking agent (B) used. The crosslinking temperature is preferably 170° C. or less.
[0066] <Adhesive layer> The adhesive can be laminated as an adhesive layer on various substrates. The thickness of the adhesive layer is preferably 5 to 300 μm, more preferably 10 to 200 μm, and even more preferably 20 to 150 μm. If the adhesive layer is too thin, the thickness precision tends to decrease and the adhesive strength tends to decrease, and if it is too thick, the adhesive film tends to protrude from the edge when rolled.
[0067] The gel fraction of the pressure-sensitive adhesive layer is preferably 0.1 to 99% by weight, more preferably 1 to 90% by weight, and even more preferably 10 to 80% by weight, from the viewpoints of adhesion to the substrate, reworkability, and holding power. If the gel fraction is too low, the cohesive strength is low, and there is a tendency for adhesive residue to remain during rework and for holding power to be low, whereas if the gel fraction is too high, there is a tendency for the adhesive strength to be too low and for the adhesive to be easily peeled off.
[0068] The gel fraction is a measure of the degree of crosslinking (degree of curing) and is calculated, for example, by the following method: An adhesive is picked from an adhesive film having an adhesive layer formed on a substrate, the adhesive is wrapped in a 200-mesh SUS wire netting and immersed in toluene at 23°C for 24 hours, and the weight percentage of the insoluble adhesive component remaining in the wire netting relative to the weight of the adhesive before immersion in toluene is defined as the gel fraction.
[0069] The pressure-sensitive adhesive layer preferably has a moderate tackiness when touched with a finger, since this tends to improve workability due to good wettability when actually applied to an adherend. Tackiness is measured by ball tack at an inclination angle of 30° as specified in JIS Z0237 (2009). Ball tackiness is preferably 1 or more, more preferably 3 or more. If the ball tackiness is too low, the pressure-sensitive adhesive film tends to be difficult to adhere to the adherend when it is applied to the adherend.
[0070] <Adhesive film> The pressure-sensitive adhesive film of the present invention is obtained by laminating the above-mentioned pressure-sensitive adhesive layer on a substrate film such as a plastic film. It is preferable that the pressure-sensitive adhesive film further has a release film provided on the surface opposite to the surface on which the base film is laminated to the pressure-sensitive adhesive layer.
[0071] Examples of the base film include polyester resins such as polyethylene terephthalate, polyolefins such as polyethylene, and polyurethanes.
[0072] Examples of methods for producing the above-mentioned adhesive film include (1) a method in which an adhesive composition is applied onto a base film, dried, a release film is laminated, and at least one of aging treatments is performed at room temperature or at an elevated temperature, and (2) a method in which an adhesive composition is applied onto a release film, dried, a base film is laminated, and at least one of aging treatments is performed at room temperature or at an elevated temperature. Among these, the above method [2], in which aging is performed at room temperature (23° C.), is preferred since it does not damage the base film due to heat and provides excellent adhesion between the base film and the pressure-sensitive adhesive layer.
[0073] Such aging treatment is carried out to balance the adhesive properties as the reaction time of the chemical crosslinking of the adhesive, and the aging conditions are usually a temperature of 20 to 70°C and a time of 1 to 30 days, and specifically, for example, 23°C for 3 to 10 days or 40°C for 1 to 7 days.
[0074] When applying the pressure-sensitive adhesive composition, it is preferable to dilute the pressure-sensitive adhesive composition with a solvent before application. The dilution concentration is preferably such that the heating residue (solid content concentration) is 5 to 60% by weight, and particularly preferably 10 to 30% by weight.
[0075] The solvent is not particularly limited as long as it dissolves the pressure-sensitive adhesive composition, and examples of the solvent that can be used include ester solvents such as methyl acetate, ethyl acetate, methyl acetoacetate, and ethyl acetoacetate, ketone solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone, aromatic solvents such as toluene and xylene, and alcohol solvents such as methanol, ethanol, and propyl alcohol. Among these, ethyl acetate and methyl ethyl ketone are preferably used in terms of solubility, drying property, cost, etc. These may be used alone or in combination of two or more kinds.
[0076] The pressure-sensitive adhesive composition can be applied by a conventional method such as roll coating, die coating, gravure coating, comma coating, or screen printing.
[0077] The above adhesive film is aged at 40°C for 3 days, and then a 25 mm x 100 mm test piece is prepared. The test piece is pressed and attached to a stainless steel plate (SUS304BA plate) whose surface has been wetted with purified water using a 2 kg rubber roller in two passes at 23°C and a relative humidity of 50%. The test piece is then left to stand in the same atmosphere for 30 minutes, and the adhesive strength when peeled off at a peel angle of 180° and a peel speed of 300 mm / min is preferably 5.0 N / 25 mm or more, and more preferably 9.0 N / 25 mm or more.
[0078] The pressure-sensitive adhesive film of the present invention is used by laminating the pressure-sensitive adhesive layer surface to the surface of an adherend, either directly or, in the case of a film having a release film, after removing the release film.
[0079] The adhesive film of the present invention shows sufficient adhesive performance even under water or wet conditions, and furthermore, when it is peeled off after being adhered to an adherend, it is possible to prevent the occurrence of adhesive residue and sticking marks on the surface of the adherend, so it is also excellent in the resistance to contamination of the adherend. Therefore, it can be suitably used as an adhesive film for various members such as a surface protection film, a display label, a masking tape, an adhesive film for a touch panel, an adhesive film for a sensor such as ITO, an adhesive film for an in-vehicle use, an optical film, and a polarizing plate, and is particularly suitable for use as an adhesive film for masking, particularly as a masking tape (masking tape) for construction. EXAMPLES
[0080] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the invention. In the examples, "parts" and "%" are by weight.
[0081] First, the following materials were prepared prior to the experiment.
[0082] <Acrylic resin> Acrylic resins (A-1) to (A-6) and (A'-1) were prepared according to the preparation methods described below. The composition and physical properties of each acrylic resin are shown in Table 1 below. The weight average molecular weight (molecular weight Mw), dispersity, and glass transition temperature (Tg) of the above acrylic resin shown in Table 1 were measured according to the above-mentioned methods. The viscosity shown in Table 1 was measured according to the viscometer method using a Brookfield type rotational viscometer in accordance with JIS K7117-1 (1999). The acrylic monomers (a) [(a1-1), (a1-2)] prepared as materials for the respective acrylic resins are monomers represented by the following chemical formula.
[0083] [ka]
[0084] The acrylic monomers (a1-1) and (a1-2) were synthesized as follows.
[0085] [Synthesis of acrylic monomer (a1-1)] After attaching a dropping funnel to a three-necked flask containing a rotor, 2-hydroxyethyl methacrylate (95.0 g, 0.73 mol) was placed in the flask and dissolved in tetrahydrofuran (1000 mL), and triethylamine (89.2 g, 0.88 mol) was added. The mixture thus obtained was cooled to 0°C, and then methanesulfonyl chloride (101.5 g, 0.89 mol) was placed in the dropping funnel and slowly dropped into the mixture. After the dropwise addition, the mixture was reacted at 25°C for 16 hours. Next, water (800 mL) was added to the mixture after the reaction, and the product was extracted into the organic layer with ethyl acetate (800 mL x 3 times). The ethyl acetate solution was washed with water (800 mL) and brine (800 mL) in that order, and dehydrated with anhydrous sodium sulfate. Then, the solvent was removed with an evaporator to obtain methanesulfonic acid-2-ethyl methacrylate (yellow liquid, 151.0 g).
[0086] In addition, the above-mentioned yellow liquid 1 The results of analysis by 1 H NMR were as follows: 1H NMR (400MHz, CDCl3): δ=6.08(s, 1H), 5.57-5.54(m, 1H), 4.41-4.37(m, 2H), 4.35-4.31(m, 2H), 2.98(s, 3H), 1.88(s, 3H)
[0087] In addition, a three-neck flask equipped with a rotor was charged with gallic acid (36.0 g, 0.21 mol) and sodium hydrogen carbonate (43.0 g, 0.51 mol), and DMSO (300 mL) was added to prepare a mixture. The methanesulfonic acid-2-ethyl methacrylate (36.7 g, 0.18 mol) obtained as above was added thereto at room temperature, and the mixture was reacted at 80° C. for 16 hours. The reaction solution was returned to room temperature, water (300 mL) and 1N hydrochloric acid solution (70 mL) were added, and the product was extracted into the organic layer with ethyl acetate (400 mL x 3 times). The ethyl acetate solution was washed with water (400 mL) and brine (500 mL) in that order, and dehydrated with anhydrous sodium sulfate. The solvent was then removed with an evaporator, purified by column chromatography (packing material: silica gel, solvent: hexane / ethyl acetate mixture), and further recrystallized with a solution of ethyl acetate / n-heptane = 1 / 8 (270 mL) to obtain acrylic monomer (a1-1) (white solid, 26.0 g).
[0088] In addition, the above-mentioned white solid 1 The results of analysis by 1 H NMR were as follows: 1 H NMR (400MHz, DMSO-d6): δ=9.22(s, 3H), 6.94(s, 2H), 6.05-6.02(m, 1H), 5.71-5.67(m, 1H), 4.46-4.36(m, 4H), 1.87(t, 3H)
[0089] [Synthesis of acrylic monomer (a1-2)] After attaching a dropping funnel to a three-necked flask containing a rotor, 4-(chloroacetyl)catechol (75.0 g, 0.40 mol) and methacrylic acid (76.1 g, 0.88 mol) were placed in the flask and dissolved in acetonitrile (1200 mL). The mixture thus obtained was cooled to 0°C, and then triethylamine (85.4 g, 0.84 mol) was placed in the dropping funnel and slowly dropped into the mixture under a nitrogen stream. After dropping, the mixture was reacted at 80°C for 20 hours. The mixture after the reaction was returned to room temperature, a 2N aqueous hydrochloric acid solution was added until the pH reached 4, water (1000 mL) was added, and the product was extracted into an organic layer with dichloromethane (1100 mL x 2 times). The dichloromethane solution was dehydrated with anhydrous sodium sulfate, the solvent was removed with an evaporator, and the product was purified by column chromatography (packing material: silica gel, solvent: hexane / ethyl acetate mixture) to obtain an acrylic monomer (a1-2) (white solid, 46.7 g).
[0090] In addition, the above-mentioned white solid 1 The results of analysis by 1 H NMR were as follows: 1 H NMR (400MHz, DMSO-d6): δ=10.45-9.27(m, 2H), 7.43-7.28(m, 2H), 6.84(d, 1H), 6.12(s, 1H), 5.77(t, 1H), 5.42(s, 2H), 1.93(s, 3H)
[0091] [Preparation of acrylic resin (A-1)] In a four-necked round-bottom flask equipped with a reflux condenser, a stirrer, a nitrogen gas inlet, and a thermometer, 91 parts of n-butyl acrylate (BA), 8 parts of acrylic acid (AAc), and 1 part of acrylic monomer (a1-1), which are copolymerization components (monomers) of the acrylic resin (A-1), were charged, and further, 45 parts of methyl ethyl ketone, 45 parts of acetone, and 0.038 parts of 2,2'-azobisisobutyronitrile (AIBN) as a polymerization initiator were charged, and the temperature was raised while stirring, and the internal temperature was raised to the boiling point to start the reaction. Next, 33.8 parts of a methyl ethyl ketone solution containing 0.023% AIBN was dropped over 2 hours. Furthermore, during the polymerization, a mixed solution of 33.8 parts of methyl ethyl ketone and 0.023 parts of AIBN and a mixed solution of 25 parts of methyl ethyl ketone and 0.015 parts of AIBN were successively added and reacted under reflux for 7.5 hours to obtain a solution of acrylic resin (A-1).
[0092] [Preparation of acrylic resins (A-2) to (A-6)] The monomer composition was changed as shown in Table 1 below. Except for that, polymerization was carried out in accordance with the preparation method of the above acrylic resin (A-1) to obtain an acrylic resin solution.
[0093] [Preparation of acrylic resin (A'-1)] In a reactor equipped with a thermometer, a stirrer, a dropping funnel and a reflux condenser, 61.3 parts of ethyl acetate and 0.037 parts of 2,2'-azobisisobutyronitrile (AIBN) were charged, and the internal temperature was raised to the boiling point while stirring, and then a mixed solution of 91.9 parts of n-butyl acrylate (BA), 8 parts of acrylic acid (AAc), and 0.1 parts of 2-hydroxyethyl methacrylate (HEMA), which are copolymerization components (monomers) of acrylic resin (A'-1), was dropped over 2 hours. Furthermore, during the polymerization, 0.08 parts of AIBN was added to 13.3 parts of toluene, and the mixture was reacted under reflux for 6.0 hours, and then diluted with 90.68 parts of ethyl acetate and 2.03 parts of toluene to obtain a solution of acrylic resin (A'-1).
[0094] [Table 1]
[0095] <Epoxy-based crosslinking agent (B)> Multifunctional epoxy resin (B-1): TETRAD-C (manufactured by Mitsubishi Gas Chemical Company, Inc.)
[0096] [Example 1] [Preparation of Pressure-Sensitive Adhesive Composition] 0.1 part of an epoxy-based crosslinking agent (B-1) was mixed with 100 parts of the solid content of the acrylic resin (A-1) obtained above to prepare a pressure-sensitive adhesive composition.
[0097] [Preparation of adhesive film] The adhesive composition prepared above was applied to a PET film (thickness 38 μm) substrate so that the adhesive layer would have a thickness of about 25 μm after drying, and then dried for 2 minutes at 100° C. Thereafter, a release-treated PET film (release film: thickness 38 μm) was attached to the coated surface to protect the adhesive layer, and an adhesive film was produced. The obtained adhesive film was evaluated for the following properties, and the results are shown in Table 2 below.
[0098] ≪Adhesive force≫ (Adhesion to dry surfaces) The adhesive film obtained above was aged for 3 days at 40°C, after which a 25mm x 100mm test piece was prepared. The release film was then peeled off and the piece was pressed and attached to a stainless steel plate (SUS304BA plate) using a 2kg rubber roller in two passes back and forth at 23°C and a relative humidity of 50%. The piece was then left to stand for 30 minutes in the same atmosphere, after which the 180 degree peel strength (N / 25mm) was measured at a peel speed of 300mm / min.
[0099] (Adhesion to wet surfaces) The adhesive film obtained above was aged at 40°C for 3 days, and then a 25mm x 100mm test piece was prepared. The release film was removed and the piece was pressed and attached to a stainless steel plate (SUS304BA plate) whose surface had been wetted with purified water using a 2kg rubber roller in two passes at 23°C and a relative humidity of 50%. The piece was then left to stand for 30 minutes in the same atmosphere, after which the 180° peel strength (N / 25mm) was measured at a peel speed of 300mm / min and evaluated according to the following criteria. (Evaluation Criteria) ○...9.0N / 25mm or more △ 5.0N / 25mm or more, less than 9.0N / 25mm ×...Less than 5.0N / 25mm
[0100] ≪Stain resistance (wet surface)≫ The adhesive film obtained above was aged for 3 days at 40°C, and then prepared into a 25mm x 100mm test piece. The release film was removed and the test piece was pressed and attached to a stainless steel plate (SUS304BA plate) whose surface had been wetted with purified water using a 2kg rubber roller in two passes at 23°C and a relative humidity of 50%. The test piece was then left to stand for 30 minutes in the same atmosphere, after which the condition of the adherend surface after 180° peeling at a peeling speed of 300mm / min was observed and evaluated according to the following criteria. (Evaluation Criteria) ○: No adhesive residue was observed ×: Adhesive residue was observed
[0101] [Examples 2 to 6, Comparative Example 1] Pressure-sensitive adhesive compositions were prepared and pressure-sensitive adhesive films were produced in the same manner as in Example 1, except that the acrylic resins shown in Table 2 below were used. Using the obtained pressure-sensitive adhesive compositions and pressure-sensitive adhesive films, evaluations were carried out in the same manner as in Example 1. The results are also shown in Table 2 below.
[0102] [Table 2]
[0103] The results in Table 2 above show that the examples have excellent adhesion to wet surfaces, whereas the comparative examples, which used acrylic resins that did not contain monomers of a specific structure as copolymerization components, had poor adhesion to wet surfaces. This also shows that it is important that the acrylic resin contains a monomer having a specific structure as a copolymerization component.
[0104] Furthermore, the adhesive compositions of the examples also have good resistance to contamination on wet surfaces, and are therefore suitable for use as adhesives for masking films and masking adhesive films. [Industrial Applicability]
[0105] The adhesive obtained from the adhesive composition using the acrylic resin of the present invention can provide an adhesive composition that can exhibit sufficient adhesive performance even in water or under wet conditions. Therefore, it can be suitably used as an adhesive for various members such as an adhesive for masking films, an adhesive for surface protection films, an adhesive for display labels, an adhesive for masking tapes, etc., and is particularly suitable for use as an adhesive for masking films, particularly as an adhesive for architectural masking films.
Claims
1. A pressure-sensitive adhesive composition comprising: an acrylic resin (A) obtained by copolymerizing a copolymerization component (a) containing an acrylic monomer (a1-1) represented by the following chemical formula (1) and / or an acrylic monomer (a1-2) represented by the following chemical formula (2); and a crosslinking agent (B). 【Chemistry 1】 【Chemistry 2】
2. 2. The pressure-sensitive adhesive composition according to claim 1, wherein the total ratio of the acrylic monomer (a1-1) and the acrylic monomer (a1-2) in the copolymerization component (a) is 0.01 to 50% by weight.
3. A pressure-sensitive adhesive obtained by crosslinking the pressure-sensitive adhesive composition according to claim 1 or 2.
4. An adhesive film comprising an adhesive layer comprising the adhesive according to claim 3.
5. A masking adhesive comprising the adhesive according to claim 3.
6. A masking adhesive film comprising the adhesive according to claim 3.
Citation Information
Patent Citations
Polymeric scavengers for oxidized developing agents and photographic elements containing same
JP1994509880A
Water dispersion-type adhesive composition and adhesive product
JP2003313525A
Positive resist composition and method for forming pattern by using the same
JP2006091662A
Catechol group containing polymer
JP2014065857A
Adhesive sheet for wet surfaces, and concrete structure
JP2017160344A